National Identity in Southeast Asia: A Critique on Anthony Reid’s work - Quang Anh, Phan (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Southeast Asia is a changing region. In terms of Nationalism, a modern and dynamic Southeast Asia has sought for a re-determination of its post-colonial status and expressed an endeavor building up a coherent entity by forming a nation block, the ASEAN. Many scholars have touched upon this topic by approaching it from various perspectives, with or without considering its indigenous agency which is unique for its context. Anthony Reid seems to be among those who stand on the side of people who dissect the contested nature of identity in Southeast Asia today through a fusion of external factors-western colonialism and internal factors. Through a content analysis of his recent book on this matter, this paper aims to clarify his view as well as point out some issues in his arguments which should be seen through a wider lens. Received: 8th October 2015; Revised: 9th December 2015; Accepted: 28th December 2015